ANALISIS KOMPARATIF PENDAPAT IMAM MALIK DAN IMAM SYAFI’I TENTANG KEDUDUKAN KHULU’ SEBAGAI TALAK - Fauzaan Fadhurrohman Zaenal; Andi Muhammad Akmal; Muh. Jamal Jamil; Andi Haerur Rijal (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This study aims to analyze the opinions of Imam Malik and Imam al-Shafi‘i regarding the legal position of khulʿ in Islamic marital law, particularly whether it should be classified as talaq or fasakh. The research employs a qualitative approach through library-based normative-doctrinal analysis, focusing on primary sources such as al-Muwattaʾ and al-Mudawwanah al-Kubra by Imam Malik, as well as key texts from the Shafi‘i school. Secondary data are obtained from relevant classical and contemporary literature. A descriptive-comparative method is applied to examine the underlying legal reasoning of both scholars and its implications in contemporary contexts. The findings reveal that Imam Malik views khulʿ as a form of talaq, resulting in a reduction in the number of permissible divorces and granting the husband the right of revocation during the waiting period (ʿiddah). In contrast, Imam al-Shafi‘i categorizes khulʿ as fasakh, thereby permanently dissolving the marriage without the right of revocation. Supporting Imam Malik’s position, the study argues that although initiated by the wife with compensation (ʿiwad), the legal formula of khulʿ remains the prerogative of the husband, making its classification as talaq more consistent. If considered fasakh, khulʿ would paradoxically function as a dissolution mechanism that reinforces the husband’s authority rather than reflecting the wife’s will. Overall, this study contributes to contemporary fiqh discourse on mechanisms of marital dissolution within Islamic law.